Testing different ensiling parameters to increase butyric acid concentration for maize silage, followed by silage separation and methane yield potential of separated solids residues. (September 2019) - Steinbrenner, Jörg; Nägele, Hans-Joachim; Buschmann, Annette; Hülsemann, Benedikt; Oechsner, Hans
Abstract: In a Green Biorefinery system, the production of organic acids, fibres and biogas is in focus. Silage is separated into a press juice and press cake. During the ensiling process, organic acids like lactic acid, acetic acid and butyric acid can be formed, depending on the used substrate and ensiling conditions. Different treatments were applied to maize to increase the butyric acid content. The silage was separated and the specific methane yield of the resulting press cake was measured. The combination of an increased buffering capacity through carbonated lime and a low dry matter content leads to high butyric acid concentrations of up to 75.06 g kg −1 DM in the silage. Silage separation with this treatment resulted in an 18% loss in the methane yield per hectare. Graphical abstract: Unlabelled Image Highlights: Two storage temperatures (20 °C; 37 °C) were tested. Resulting silage was separated to a press juice and press cake. A butyric acid concentration of 22.7 g kg −1 was achieved in the press juice. The specific methane yield of the press cake (residues) was determined.